A retrospective analysis of oral and maxillofacial pathology in an Australian paediatric population. (June 2014) - Ha, WN; Kelloway, E; Dost, F; Farah, CS
Abstract Background The prevalence of oral and maxillofacial pathology has not previously been reported in the Australian paediatric population. This study aimed to audit a large pathology service to provide insight into the prevalence of oral and maxillofacial pathology. Methods Written records of a major Australian oral pathology service were imported into an electronic database. Age, gender and histological diagnosis were assessed. Prevalence of histological diagnoses as a percentage of the major diagnostic categories and of the whole sample were calculated, as well as gender predilections and mean age of presentation of disease. Results A total of 1305 oral pathology specimens, collected from paediatric patients aged 16 and under were included in the analysis. The most common pathology was dental pathology (24.4%), followed by odontogenic cysts (18.5%) and mucosal pathology (17.0%). The most frequently encountered lesion was the dentigerous cyst (9.4%), followed by fibrous hyperplasia (8.3%), radicular cyst (5.2%) and chronic periapical granuloma (5.2%). Conclusions In the paediatric population, dental pathology and specifically, the dentigerous cyst is the most common pathology type sent for histopathology, suggesting a high prevalence of pathology of dental origin occurring in Australian children.